Peningkatan Keterampilan Berdiskusi melalui Model Pembelajaran Teknik Two Stay Two Stray pada Siswa Kelas VIII C SMP Jagakarsa - Saragih, Dasmay Sena; Suhardjono, Dadi Waras; Asuti, Tri (Jurnal Bahastra, 2024)
The research was carried out using Classroom Action Research (PTK) which used two cycles. Each cycle consists of two meetings. The research subjects were 25 students in class VIII C of Jagakarsa Middle School. The variable revealed in the research is Discussion Skills Through the Two Stay Two Stray Technique Learning Model. Data collection techniques use test instruments and non-test instruments in the form of observation, interviews, questionnaires and documentation. The results of the research show an increase in poetry writing discussion skills using the Two Stay Two Stray technique learning model in class VIII C of Jagakarsa Middle School. The percentage of students' completion in writing poetry in the pre-cycle reached 28% and was still less than the set standard for completion, namely 75%. The percentage of completion in cycle I reached 48%. This is also still less than the specified completion limit. In cycle II the percentage of completion reached 80% and had met the specified completion limit.